PENCURIAN KOLEKSI MUSEUM NEGERI PROVINSI SULAWESI TENGGARA: SEBUAH REFLEKSI PERMASALAHAN KEAMANAN MUSEUM DI INDONESIA - M. Sabri; Wa Ode Rawianti (SANGIA: Jurnal Penelitian Arkeologi, 2023)
Cases of theft of museum collections in Indonesia have occurred in a number of museums, both in urban centers and in regional areas. The State Museum of Southeast Sulawesi Province did not escape the theft of museum collections that occurred in early 2021. This research attempts to describe the security conditions of the State Museum of Southeast Sulawesi Province before and after the theft occurred at the museum. This research uses library methods and field observations to obtain the required information. Based on the results of the research, it is known that there are 900 museum collections stolen by unknown parties. The condition of the museum before the theft occurred was known to have a security system that was not optimal as evidenced by the absence of control by museum supervisors or CCTV security. The condition of the museum after the theft has experienced a number of improvements in the form of iron bars and locks on a number of doors and windows of the museum building. However, based on field observations, security at the museum is still far from properly implementing the concept of museum security.